THE METHOD OF IMAGINARY MAP FOR HIGHER GEOGRAPHY LITERACY IN GENDER PERSPECTIVE - Rahma, Isma Yullia; Yani, Ahmad; Waluya, Bagja; Ridwana, Riki (Indonesia University of Education, 2020)
The objectives of this study were (1) to compare the differences in perceptual tendencies between male and female students, (2) to analyze the opportunities for the effectiveness of the application of the imaginary map method in the classroom from a gender perspective. The total population of this study was 46 students of Geography Education, Universitas Pendidikan Indonesia, with a gender ratio of 50:50. Data were obtained by using literature study and questionnaire methods, and data analysis used was quantitative and qualitative. From the research, data are acquired that there is a general tendency for the same perception between genders, but the difference is that female has a wider and different level of object perception. Although there was a majority of answers to object perception, about 40% of students have a completely different perception of an object. Therefore, to be applied to the classroom, the teacher can work around by providing an imaginary map with the shape of an object that has been given a bold line, so that the image given to students can be more purpose-driven kind of attention. Furthermore, it is necessary to examine the method of the imaginary map directly to students who currently studying map material in class, as well as the need to develop imaginary objects for maps of all countries.